Wilayah Pelayanan dan Aksesibilitas Taman Kota bagi Lansia di Kota Denpasar - I Gede Bintang Nararya Sena; Ngakan Ketut Acwin Dwijendra; Tri Anggraini Prajnawrdhi (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2021)
The consistent annual increase in the number of mature population emphasizes the importance of humane and elderly-friendly urban planning. This type of planning requires an integrated approach that embraces three – but not limited – main urban elements, namely open space, settlement, and transportation. In its attempt to review available planning regulations and practices, this research studies elderly groups’ access to urban parks that are available across Denpasar City. Within, the service area is used as a tool to measure accessibility. The scale of this service area is analyzed based on a pareto distribution frequency of distance traveled before reaching a city park. This data is presented in a map using geospatial analysis which leads to the two categorizations of the primary and secondary service area. This study finds that Niti Mandala Renon City Park possesses the most extensive service area followed by Puputan Badung and Lumintang City Park. Mature park users go to these parks for both recreational and sport-related reasons. In doing so, they choose to travel by private modes of transportation. The elderly group also tends to visit with family member/s, especially when they aim for a park whose scale of the service area is extensive and that requires them to have a relatively long drive from home. This practice is frequently attributed to safety and cultural reasons. Keywords: urban planning, City parks, accessibility, elderly Abstrak Pertambahan jumlah lansia yang konsisten setiap tahunnya menimbulkan kepentingan perencanaan kota yang ramah lansia. Berdasarkan prinsip perencanaan kota ramah lansia dan humanis, perencanaan kota perlu memadukan aspek ruang terbuka hijau, permukiman dan transportasi. Untuk dapat melakukan tinjauan mengenai perencanaan tersebut dilakukan penelitian mengenai aksesibilitas ruang terbuka hijau publik bagi lansia di Kota Denpasar dalam konteks perencanaan kota ramah lansia. Wilayah pelayanan merupakan salah satu cara untuk mengukur aksesibilitas ruang terbuka hijau. Hal tersebut ditelaah menggunakan analisis distribusi pareto frekuensi jarak tempuh lansia menuju taman kota yang diterjemahkan kedalam peta menggunakan analisis geospasial. Wilayah pelayanan dibagi menjadi wilayah pelayanan primer dan sekunder berdasarkan frekuensi data jarak tempuh lansia menuju taman kota. Penelitian menemukan bahwa taman kota dengan wilayah pelayanan paling luas adalah Taman Kota Niti Mandala Renon disusul Taman Kota Puputan Badung dan Taman Kota Lumintang. Seluruh lansia pengunjung taman kota merupakan lansia yang bertujuan untuk melakukan kegiatan olahraga rekreasi, dan memilih untuk melakukan perjalanan menggunakan moda transportasi pribadi. Taman kota dengan wilayah pelayanan yang luas dan jarak perjalanan yang jauh, lansia melakukan perjalanan dengan keluarga. kecenderungan ini dapat dikaitkan dengan keamanan dan budaya komunalitas lansia. Kata kunci: perencanaan kota, taman kota, aksesibilitas, lansia